Adoption of Artificial Intelligence Technology in Human Resource Management in Digital Office Management - Yuliana, Marcha Dwi; Mardianti, Febri (International Journal Administration, Business & Organization, 2025)
The objective of this research is to examine the impact of integrating Artificial Intelligence (AI) on the effectiveness of Human Resource Management (HRM) within a digital office workplace. The study reveals that AI enhances the efficiency, accuracy, and fairness of numerous HR operations, especially recruitment, performance evaluation, and staff development. This research employs a qualitative descriptive approach using a systematic literature review to synthesize relevant scholarly findings on AI adoption in HRM within digital office environments. Furthermore, the implementation of digital technologies promotes enhanced communication, faster information flow, and a collaborative and inventive working environment. Despite these benefits, challenges remain, such as data privacy issues, cybersecurity threats, employees’ insufficient digital literacy, and resistance to technological innovation. Successful AI implementation in human resource management requires a holistic strategy encompassing technological readiness, enhancement of employees’ digital competencies, adherence to ethical standards, and an adaptable organizational culture. This approach allows organizations to develop flexible, sustainable, and effective office management systems that preserve a competitive edge amidst ongoing digital transformation.